Traditional Chinese medicine promotes the control and treatment of dementia - Pengyu Tao; Wenxin Xu; Simeng Gu; Haiyan Shi; Qian Wang; Yuzhen Xu (Frontiers Media S.A., 2022)
Dementia is a syndrome that impairs learning and memory. To date, there is no effective therapy for dementia. Current prescription drugs, such as cholinesterase inhibitors, fail to improve the condition of dementia and are often accompanied by severe adverse effects. In recent years, the number of studies into the use of traditional Chinese medicine (TCM) for dementia treatment has increased, revealing a formula that could significantly improve memory and cognitive dysfunctions in animal models. TCM showed fewer adverse effects, lower costs, and improved suitability for long-term use compared with currently prescribed drugs. Due to the complexity of ingredients and variations in bioactivity of herbal medicines, the multi-target nature of the traditional Chinese formula affected the outcome of dementia therapy. Innovations in TCM will create a platform for the development of new drugs for the prevention and treatment of dementia, further strengthening and enhancing the current influence of TCM.